Sustainable development and international marketing strategies in a globally operating company: Case study - Mustola, Eveliina (My University, 2023)
Companies worldwide are struggling to adapt to their new role, which requires meeting present needs without compromising the ability of future generations to meet their own needs. They are called upon to take responsibility for the impact of their actions on people and the environment and incorporate sustainable development concepts into their practices. However, the procreation of ecolabels, whether self-declared or endorsed by third parties, poses challenges for consumers in distinguishing genuinely responsible businesses. This situation undermines the effectiveness of corporate social responsibility initiatives, even for genuinely accountable companies. It also leads to marketing communication issues such as green claims, greenwashing, and uncertainties about the transparency and sustainability of companies' supply chains. However, due to unclear regulations, not all consumers are aware of these phenomena or take the time to understand the complete journey of products or sustainability-related aspects like packaging and environmental goals of companies. The purpose of this study is to explore how globally operating company with sustainable development strategies tackle ethical challenges in international marketing. It aims to investigate the marketing strategies used by these companies, as well as the regulations and certifications they follow, to prevent any accusations of greenwashing. The study also investigates what challenges the globally operating company might face when it implements these strategies in its sub-countries. Thus, the research focuses on the intersection of sustainability, ethics, and international marketing. The research question will be: “How do international companies implement ethical and sustainable global marketing strategies?”. The research objectives were formulated to comprehend these concerns and how the selected case company has addressed these issues. The theoretical framework and key concepts completed using data from secondary sources related above mentioned topics. The empirical part was conducted using qualitative semi-structured one-to-one interviews with six selected case company representatives. The main results of the research show that globally operating company must implement these strategies into its overall operations. Moreover, sustainability is not only marketing department’s task - but it should also be part of company’s DNA. Continuous internal communication and guidelines helps to avoid greenwashing. Besides that, communication must be transparent, and data based. In addition, local needs must be considered and adapt strategies in each country, because international marketing is complex, and maturity of markets and customer needs vary a lot.

Yritykset ympäri maailmaa pyrkivät sopeutumaan uuteen rooliin, jossa niiden on otettava vastuu toimintansa vaikutuksista ihmisiin ja ympäristöön sekä sisällytettävä kestävän kehityksen käsitteet osaksi strategiaansa. Erilaisten ympäristömerkkien lisääntyminen asettaa kuluttajille haasteita tunnistaa aidosti vastuullisesti toimivat yritykset. Tämä johtaa myös epäeettisiin toimiin markkinointiviestinnässä, kuten viherpesuun. Lisäksi epävarmuus yritysten toimitusketjujen läpinäkyvyydestä ja vastuullisuudesta lisääntyy. Kaikki kuluttajat eivät kuitenkaan ole tietoisia edellä mainituista ilmiöistä. Tämän tutkimuksen tarkoituksena on tarkastella, miten maailmanlaajuisesti toimivat yritykset, joilla on kestävän kehityksen toimintastrategia, ovat vastanneet eettisiin ja kestävään kehitykseen liittyviin haasteisiin kansainvälisessä markkinoinnissa. Tutkimuksen tavoitteena on tutkia case-yrityksen käyttämiä markkinointiviestintästrategioita sekä säädöksiä ja sertifiointeja, joita yritys noudattaa välttääkseen mahdollisen viherpesun. Tutkimuksessa selvitetään myös, millaisia haasteita maailmanlaajuisesti toimiva yritys voi kohdata, kun se implementoi näitä strategioita tytäryhtiöissään eri maissa. Tutkimuksessa keskitytään kestävän kehityksen, etiikan ja kansainvälisen markkinoinnin risteyskohtiin. Tutkimuksen tavoitteena on vastata kysymykseen "Miten kansainväliset yritykset toteuttavat eettisiä ja kestäviä maailmanlaajuisia markkinointistrategioita?". Tutkimus toteutettiin laadullisena haastattelututkimuksena, jossa haastattelutavaksi valittiin puolistrukturoitu teemahaastattelu. Tutkimuksessa haastateltiin kuutta valitun case-yrityksen asiantuntijaa, jotka työskentelevät kestävän kehityksen ja kansainvälisen markkinoinnin parissa. Tutkimuksen tärkeimmät tulokset osoittavat, että maailmanlaajuisesti toimivan yrityksen on implementoitava nämä strategiat osaksi koko toimintaansa. Kestävä kehitys ei ole vain markkinointiosaston tehtävä, vaan sen pitäisi olla osa yrityksen DNA:ta. Yrityksen jatkuva sisäinen viestintä sekä yhteiset suuntaviivat auttavat välttämään viherpesua. Lisäksi viestinnän on oltava läpinäkyvää sekä dataan perustuvaa. Näiden lisäksi yrityksen on otettava huomioon alueelliset vaatimukset ja mukautettava strategioita kussakin maassa. Kansainvälinen markkinointi on monitahoista, sillä markkinoiden kypsyys ja asiakkaiden tarpeet vaihtelevat huomattavasti eri maiden välillä.
Keywords: sustainable development; marketing communication; greenwashing; societal responsibility; international corporations; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business